2005
DOI: 10.1128/aem.71.8.4885-4887.2005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Campylobacter Bacteriophage with Reduced Presence of Hosts in Broiler Chicken Ceca

Abstract: Campylobacter jejuni and Campylobacter-specific bacteriophage were enumerated from broiler chicken ceca selected from 90 United Kingdom flocks (n = 205). C. jejuni counts in the presence of bacteriophage (mean log10 5.1 CFU/g) were associated with a significant (P < 0.001) reduction compared to samples with Campylobacter alone (mean log10 6.9 CFU/g)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…Despite the absence of in vitro susceptibility in isolates of field trial 1, a reduction took place. Other experimental studies in chickens found phages hardly ever lysing Campylobacter isolates of the same source in vitro (16,32,39). Nevertheless, phage findings are associated with reduced numbers of Campylobacter (16,39).…”
Section: Reduction Of Campylobactermentioning
confidence: 94%
See 2 more Smart Citations
“…Despite the absence of in vitro susceptibility in isolates of field trial 1, a reduction took place. Other experimental studies in chickens found phages hardly ever lysing Campylobacter isolates of the same source in vitro (16,32,39). Nevertheless, phage findings are associated with reduced numbers of Campylobacter (16,39).…”
Section: Reduction Of Campylobactermentioning
confidence: 94%
“…Their use for reducing Campylobacter in the chicken gut has been investigated in studies with different phages, doses, experimental settings, and application routes. All currently published studies showed promising results with reductions of Campylobacter in the chicken gut of 0.5 to 5.0 log 10 CFU/g (12)(13)(14)(15)(16). Adjusting the dosing methods and timing of previous studies to the conditions in commercial broiler houses plays a major role in further developing bacteriophage-mediated biocontrol of Campylobacter (17).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The use of bacteriophages to reduce Campylobacter cecal colonization of chickens has shown encouraging results as far as reducing Campylobacter counts. A number of studies have reported that under experimental conditions, bacteriophage treatment of chickens which have already been colonized with Campylobacter results in reductions of 0.5 to 5.0 log 10 CFU/g Campylobacter in the chicken gut (410)(411)(412)(413)(414). For example, in a field trial by Kittler and colleagues, a phage cocktail at levels of 5.8 to 7.5 log 10 PFU/bird was added to the drinking water of chickens colonized with Campylobacter, and the results showed that, at slaughter, Campylobacter counts in the ceca of treated birds were significantly reduced (Ͼ3.2 log 10 CFU/g cecal content) compared with those of the control group (P ϭ 0.0011) (415).…”
Section: Reducing Campylobacter Transmission In Chickensmentioning
confidence: 99%
“…Since they are ubiquitous and their prevalence is high in the same environment where their hosts are D DAVID PUBLISHING abundant, bacteriophages can be considered good indicators of the presence of bacteria [23]. For instance it is clearly demonstrated the correlation between coliphages (phages active against Escherichia coli) and bacteria responsible of colibacillosis in animals [24].…”
Section: Introductionmentioning
confidence: 99%